Algunos «animales feroces» en el teatro venezolano Teatralidad de la violencia en la dramaturgia de los 70 en Venezuela - Dimeo-Álvarez, Carlos (MIMESIS, 2022)
This monograph studies the development of Venezuelan theater in the 70s, characterized by psychological, physical as well as verbal violence and cruelty. Throughout the decade, violence pervaded not only drama, but every sphere of social, political and cultural life in Venezuela. While these dramaturgies of violence disrupted the aesthetic field in many ways, they also interpreted the development of Venezuelan society.